Real-time intraoperative dynamics of white cataract—intraoperative optical coherence tomography–guided classification and management. Issue 4 (April 2020) - Titiyal, Jeewan S.; Kaur, Manpreet; Shaikh, Farin; Goel, Siddhi; Bageshwar, Lalit M. S.
Abstract : Intraoperative OCT–guided classification helps understand the actual intraoperative dynamics of different types of white cataract, identify true intumescent cataracts with an imminent risk of rhexis extension, and prevent rhexis-related complications. Abstract : Purpose: To evaluate morphological characteristics and intraoperative dynamics of different types of white cataract using intraoperative optical coherence tomography (iOCT). Setting: Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India. Design: Prospective interventional study. Methods: Fifty eyes with white cataract undergoing phacoemulsification were evaluated. The primary outcome measure was the classification of white cataract based on morphology and intraoperative dynamics on iOCT. The secondary outcome measure was rhexis-related complications. Results: Four types of white cataract were identified based on iOCT—type I (9 eyes), type II (3 eyes), type III (24 eyes), and type IV (14 eyes). Type I had regularly arranged lamellar cortical fibers, type II had continuous hyperreflective bands of cortical fibers with intralenticular clefts, type III had intralenticular clefts combined with areas of homogenous ground-glass appearance, and type IV had homogenous ground-glass appearance of the anterior lens cortex. Capsulorhexis in type I cataract was uneventful. In type II cataract, cortical bulge was observed in the anterior chamber on creating the initial nick, indicating raised intralenticular pressure (ILP) with an imminent risk of rhexis extension. A bimanual irrigation/aspiration was performed until lowering of ILP was observed on iOCT. In types III and IV, fluid release was observed on initiation of rhexis leading to partial (type III) or complete (type IV) lowering of ILP, with a mild-moderate risk of capsulorhexis extension. A continuous curvilinear capsulorhexis was achieved in all cases, with no case of posterior capsular tear or vitreous loss. Conclusions: Intraoperative OCT helped elucidate intraoperative dynamics of the spectrum of white cataracts and facilitates completion of capsulorhexis.